The impact of value co-creation on consumer citizenship behavior: Based on consumer perspective - Yang, Jialiang; Ren, Jifan; Zhao, Meihui; Chen, Haoyu; Wang, Huihan (Frontiers in Psychology, 2023)
This research investigated the value co-creation behaviors in livestreaming platforms and the internal mechanism of perceived value on consumer value co-creation behavior on the short-video platform TikTok. This research selected the Tiktok platform as the research object, and uses structural equation model to analyze consumer data. The results indicated that consumer-perceived value mediates the relationship between consumer engagement and citizenship behaviors. In addition, short-video platforms exhibit significant community attributes, and interactive behavior forms the primary part of consumer engagement that enhances the perceived value. Consumers join short-video platforms to look for communities that interest them. Consumers’ responses generate the perceived value. Thus, it enhances consumers’ intentions to continue using a particular service, which then increases the likelihood of citizenship behavior. This study also found that consumers’ creative behavior in short-video platforms embodies social and functional values. This suggested that consumers of livestreaming and short-video platforms such as TikTok tend to seek social recognition by sharing their opinions or daily lives. The examination of the mediating role of perceived value on the relationship between consumer engagement behavior and citizenship behavior revealed that perceived value significantly mediated the relationship between consumer engagement behavior and citizenship behavior. This provided evidence of the fact that consumers usually actively participate on the platform by uploading content and sharing their creations, with the motivation to generate significant social impact and gain the recognition of others. Firstly, TikTok’s consumers deeply engage on platforms in which their cognitive messages are integrated into the platform through interacting with others, browsing, and creating short videos. Secondly, TikTok provides a channel with high level of interactivity that facilitates social interaction among strangers. Video uploaders and fans develop positive interactive relationships. Thirdly, TikTok viewers may become video providers at some point; the act of co-creation creates economic value for the platform and generates emotional, functional, and social values for its consumers.